Guiding learning through simulation in health: the transformative role of the teacher: Guiando el aprendizaje a través de simulación en salud: el papel transformador del docente | 通过模拟指导健康领域的学习：教师的变革性角色 - Milione, Hugo Fernan (2024)
The parameters to define what “a general teaching role” should be have varied in the history of higher education. The existing evidence in favor of generating spaces for controversy, questions, active and greater participation of students, guiding learning and not directing it, is overwhelming. Although the clinical simulation teacher does not escape this definition, there are still controversies as to whether there are true differences in their role compared to other areas of health teaching. In this article we intend to break down some issues that differentiate the teachers in charge of the facilitation process, such as clinical simulation, which stimulates autonomous learning, meaningful learning, vicarious learning, cooperative and reflective learning, learning in action and experiential learning.